Hydrogels Based Drug Delivery Synthesis, Characterization and Administration - Anca Onaciu; Raluca Andrada Munteanu; Alin Iulian Moldovan; Cristian Silviu Moldovan; Ioana Berindan-Neagoe (MDPI AG, 2019)
Hydrogels represent 3D polymeric networks specially designed for various medical applications. Due to their porous structure, they are able to swollen and to entrap large amounts of therapeutic agents and other molecules. In addition, their biocompatibility and biodegradability properties, together with a controlled release profile, make hydrogels a potential drug delivery system. In vivo studies have demonstrated their effectiveness as curing platforms for various diseases and affections. In addition, the results of the clinical trials are very encouraging and promising for the use of hydrogels as future target therapy strategies.